2022
DOI: 10.1177/20503121221086372
|View full text |Cite
|
Sign up to set email alerts
|

A promising future for tele-mental health in Oman: A qualitative exploration of clients and therapists’ experiences

Abstract: Objectives: Tele-mental health services can play an important role in overcoming barriers in mental health services in the Eastern Mediterranean Region. However, despite its potential, tele-mental health has not been widely adopted in Oman. This study is an exploratory investigation into the experiences of therapists and their clients in utilizing video-based tele-mental health care during the COVID-19 pandemic. Methods: A total of 19 semistructured qualitative interviews were individually conducted, it includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
1
18
0
4
Order By: Relevance
“…Longdistance travel to the facility obliges patients to pay high commuting costs. In a study by Al-Mahrouqi, respondents cited the most important advantages of telepsychiatry: reduced commuting costs and no time off work to get to medical appointments [39]. Similar results were obtained by Benudis et al In their study, the authors showed that patients cited the lack of travel and the associated significant cost reduction as one of the most important benefits of telehealth [28,40].…”
Section: Reducing Costs and Travel Time To See A Specialistsupporting
confidence: 63%
“…Longdistance travel to the facility obliges patients to pay high commuting costs. In a study by Al-Mahrouqi, respondents cited the most important advantages of telepsychiatry: reduced commuting costs and no time off work to get to medical appointments [39]. Similar results were obtained by Benudis et al In their study, the authors showed that patients cited the lack of travel and the associated significant cost reduction as one of the most important benefits of telehealth [28,40].…”
Section: Reducing Costs and Travel Time To See A Specialistsupporting
confidence: 63%
“…Another provider noted that not being able to smell one of their patients limited their assessment ability; “There may be something about cleanliness and, what can I say, if a person does not take care of himself it can be a sign of, for example, depression.” ( Gullslett et al, 2021 ). The lack of available guidance and guidelines for conducting remote assessments was recognised as a limitation by some providers ( Al-Mahrouqi et al, 2022 ; Romanchych et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, participants reported that remote consultation removed the psychological barriers of stigma ( Al-Mahrouqi et al, 2022 ; Ashcroft et al, 2021 ) and anxiety ( Frayn et al, 2021 ; Gullslett et al, 2021 ) that they associated with attending in-person consultations. A provider in one study elaborated that patients find it “less stigmatizing … they don't have to worry about running into anyone” ( Ashcroft et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations